Effect of Implantation of Cryopreserved Placental Explants on Life and Health Spans (Experimental Study) - Chub, Oleg V.; Prokopiuk, Volodymyr Yu.; Musatova, Iryna B.; Prokopiuk, Olga S. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):184.